2019
DOI: 10.1111/echo.14248
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular metabolic remodeling and accompanied dysfunction in type 2 diabetic patients: A 3D speckle tracking analysis

Abstract: Purposes The purposes of our study were to determine the risk factors related to metabolic left ventricular remodeling (LVR) in type 2 diabetes mellitus (T2DM) patients and to assess the LV function with different geometry in such population. Methods Seventy‐eight T2DM patients with normal 2D‐LVEF (≥55%) were enrolled and divided into two groups with LV normal geometry (LVN) and with LV remodeling (LVR). The control group was composed of forty age‐ and sex‐matched healthy individuals with LVN. A multifactor lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
(33 reference statements)
1
8
0
1
Order By: Relevance
“…For example, the measured 3D global longitudinal strain (GLS) of controls in some studies 14 is worse than measured 3D GLS of patients with diabetes mellitus in some other studies. 10 , 13 , 21 Furthermore, it is unclear which direction has the largest difference between patients with diabetes mellitus and controls, and whether there are any significant differences between vendors in measured strain values in these studies.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…For example, the measured 3D global longitudinal strain (GLS) of controls in some studies 14 is worse than measured 3D GLS of patients with diabetes mellitus in some other studies. 10 , 13 , 21 Furthermore, it is unclear which direction has the largest difference between patients with diabetes mellitus and controls, and whether there are any significant differences between vendors in measured strain values in these studies.…”
mentioning
confidence: 89%
“…Some studies have aimed to assess the effects of diabetes mellitus on cardiac function using 3D‐STE. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 Most of these studies reported worse myocardial deformation indexes in patients with diabetes mellitus compared with healthy controls. However, the data are not robust and somewhat heterogeneous among studies.…”
mentioning
confidence: 99%
“…The VR is found in hypertension, myocardial infarction (MI), and heart failure (HF) [3–5]. It can also be found in diabetic cardiomyopathy (DCM) and the antineoplastic drug-induced cardiotoxicity (CTX) [6,7]. A study has also shown that disease-induced VR is a complex process involving cardiomyocyte growth and death, vascular sparseness, fibrosis, inflammation, and electrophysiological remodeling [8].…”
Section: Ventricular Remodelingmentioning
confidence: 99%
“…According to the historical definition of > 15% increase in left ventricular end-systolic volume (LVESV), LVR is observed in as many as 30% of anterior myocardial infarction (MI) cases and approximately 17% of non-anterior MI cases even with timely primary coronary intervention (PCI) and the use of cardiovascular-protective drugs such as angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers, beta blockers, mineral corticoid receptor antagonists, and statins [ 4 ]. Diabetes alone is known to cause LVR [ 5 , 6 ], and in another concept of diabetes mellitus-related cardiomyopathy (DMCMP), LVR has no other cause besides DM [ 7 ].…”
Section: Introductionmentioning
confidence: 99%